Paper based lateral flow immunoassay for the enumeration of Escherichia coli in urine. Issue 10 (22nd February 2018) - Gumustas, Aysen; Caglayan, Mehmet Gokhan; Eryilmaz, Merve; Suludere, Zekiye; Acar Soykut, Esra; Uslu, Bengi; Boyaci, Ismail Hakki; Tamer, Ugur
Abstract : In this experimental study, we developed lateral flow immunoassay strips for the detection of Escherichia coli . Abstract : In this experimental study, we developed lateral flow immunoassay strips for the detection of Escherichia coli . For labelling, gold nanoparticles were prepared and modified with a Raman label. As a result of this, not only colorimetric responses but also Raman responses were obtained from the same strips. The color and Raman intensities were employed for the quantitative determination of Escherichia coli . The employment of two different detection methods strengthens the quantitative determination of Escherichia coli by lateral flow immunoassay, which is mostly used for qualitative detection or sometimes the semi-quantitative determination of samples. After careful optimization and validation steps, the developed strips allowed the highly sensitive determination of Escherichia coli in water and urine samples.